Cadmium uptake, accumulation, and remobilization in iron plaque and rice tissues at different growth stages - Zhou, Hang; Zhu, Wei; Yang, Wen-Tao; Gu, Jiao-Feng; Gao, Zi-Xiang; Chen, Li-Wei; Du, Wen-Qi; Zhang, Ping; Peng, Pei-Qin; Liao, Bo-Han (Ecotoxicology and environmental safety, 2018)
Rice consumption is considered the main source of human dietary Cd intake in Southeast Asia. This study aimed to investigate Cd uptake, accumulation, and remobilization in iron plaque and rice (Oryza sativa L. cv. ‘Xiangwanxian 12′) tissues at different growth stages. A pot experiment was performed in two Cd-contaminated paddy soils. Cd concentrations in iron plaque and rice tissues at five different growth stages (tillering, booting, milky, dough, and maturing) were measured. Cd concentrations in iron plaque and rice tissues (roots, stems, leaves, spikelet, husks, and brown rice) varied with growth stage. Cd accumulation in rice plants increased with extending growth in both soils, reaching 15.3 and 35.4μg/pot, respectively, at the maturing stage. The amounts of Cd in brown rice increased from the milky to maturing stages, with the greatest percentage uptake during the maturing stage. Cd amount in iron plaque significantly affected the uptake and accumulation of Cd in roots and aerial parts of rice plants. Accumulated Cd in leaves was remobilized and transported during the booting to maturing stages, and the contributions of Cd transportation from leaves to brown rice were 30.0% and 22.5% in the two soils, respectively. A large amount of Cd accumulated in brown rice during the maturing stage. The transportation of remobilized Cd from leaves was also important for the accumulation of Cd in brown rice. [Display omitted] •The greatest percentage uptake of Cd in rice plant was booting stage and maturing stage.•Accumulated Cd in leaves was remobilized and transported during the booting to maturing stages.•The transportation of remobilized Cd from leaves was an important contribution for Cd accumulation in brown rice.